Antimicrobial activity of Desplac® oral gel in the subgingival multispecies biofilm formation - Bueno-Silva, Bruno; Kiausinus, Karyne Rossit; Gonçalves, Francisco Jeferson dos Santos; Moreira, Marcus Vinícius Cintra; Oliveira, Eder Gonzaga de; Brugnera Junior, Aldo; Feres, Magda; Figueiredo, Luciene Cristina (Frontiers in Microbiology, 2023)
Natural products are well-known due to their antimicrobial properties. This study aimed to evaluate the antimicrobial effect of Desplac® product (composed of Aloe Vera, Propolis Extract, Green Tea, Cranberry, and Calendula) on the subgingival biofilm. Two different protocols were used to treat the 33-species biofilms: (A) 2×/day (12/12 h) for 1 min with Desplac® or Noplak Toothpaste (Chlorhexidine + Cetylpyridinium Chloride) or Oral B ProGengiva (stannous Fluoride) or a placebo gel; (B) a 12-h use of the Desplac® product or 0.12% chlorhexidine gel or a placebo gel. After 7 days of biofilm formation, the metabolic activity (MA) and biofilm profile were determined by 2,3,5-triphenyltetrazolium chloride and Checker-board DNA–DNA hybridization, respectively. Statistical analysis used the Kruskal-Wallis test followed by Dunn’s post-hoc. In protocol A, all treatments presented reduced MA compared to the placebo (p ≤ 0.05). The Desplac®-treated biofilm showed a similar microbial profile to other antimicrobials, although with higher bacterial total counts. In protocol B, MA of Desplac®-treated biofilms was lower than the placebo’s MA but higher than chlorhexidine-treated biofilms (p ≤ 0.05). Pathogen levels in Desplac®-treated biofilms were lower than in placebo-treated biofilms and elevated compared to the chlorhexidine-treated biofilms (p ≤ 0.05). Desplac® inhibited the biofilm development and disrupted the mature subgingival biofilm, highlighting its effect on Tannerella forsythia counts.